Enforcement Spillovers - Rincke, Johannes; Traxler, Christian (The Review of Economics and Statistics, 2011)
This paper identifies spillovers from law enforcement. Our approach makes use of microdata on compliance with TV license fees that allow us to distinguish between households that were subject to enforcement and those that were not. Using snowfall as an instrument for local inspections, we find a striking response of households to increased enforcement in their vicinity: on average, three detections make one additional household comply with the law. As compliance rises significantly among those who had no exposure to field inspections, our findings establish a sizable externality in enforcement.